2004
DOI: 10.1001/jama.291.19.2328
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Contrast-Induced Nephropathy With Sodium Bicarbonate

Abstract: Context Contrast-induced nephropathy remains a common complication of radiographic procedures. Pretreatment with sodium bicarbonate is more protective than sodium chloride in animal models of acute ischemic renal failure. Acute renal failure from both ischemia and contrast are postulated to occur from free-radical injury. However, no studies in humans or animals have evaluated the efficacy of sodium bicarbonate for prophylaxis against contrast-induced nephropathy. Objective To examine the efficacy of sodium bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
460
0
23

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,006 publications
(502 citation statements)
references
References 41 publications
(87 reference statements)
9
460
0
23
Order By: Relevance
“…Commentary: This trial confirms the results of the initial study by Merten et al 3 showing the superiority of bicarbonate versus saline in the prevention of CIN. That trial, published in 2004, did not use NAC.…”
Section: Results: Ufh (All Doses Compared With Control)supporting
confidence: 78%
“…Commentary: This trial confirms the results of the initial study by Merten et al 3 showing the superiority of bicarbonate versus saline in the prevention of CIN. That trial, published in 2004, did not use NAC.…”
Section: Results: Ufh (All Doses Compared With Control)supporting
confidence: 78%
“…The better efficacy of normal than half-normal saline can be explained by its enhanced ability to expand intravascular volume. A prospective, randomized single-center study of 119 patients suggested that hydration with isotonic sodium bicarbonate (154 mEq/L) 1 hr before and 6 hr after administration of contrast agent iopamidol is more effective than hydration with sodium chloride for prophylaxis of CIN (1.7% vs. 13.6%, respectively; P ¼ 0.02) [56]. It has been speculated that alkalinizing the urine reduces the nephrotoxicity of iodinated contrast media through changes in redox potential or through decreasing the viscosity of the agents within the vasa recta.…”
Section: Hydrationmentioning
confidence: 99%
“…61 Hydration with an isotonic sodium bicarbonate solution (154 mEq/L) might be superior to an equiosmolar solution of sodium chloride (154 mEq/L) at further reducing the incidence of contrast-induced nephropathy; in patients with chronic renal insufficiency, the reported incidence of contrast-induced nephropathy was 13.6% with sodium chloride hydration and 1.7% with sodium bicarbonate hydration (Pϭ.02). 62 A sodium bicarbonate solution can be prepared by adding 150 mL of 1-mEq/mL sodium bicarbonate to 850 mL of 5% dextrose in water. This solution is administered at 3.5 mL/kg for 1 hour before contrast exposure and 1.18 mL/kg/per hour for 6 hours after contrast exposure.…”
mentioning
confidence: 99%
“…Because free radical formation is promoted in an acidic environment, sodium bicarbonate is believed to attenuate contrast-induced nephropathy by increasing the pH of renal tubular fluid, thus decreasing free radical formation. 62 Recently, From et al 63 retrospectively reviewed 11,516 contrast exposures in 7977 patients and reported that sodium bicarbonate use increases the risk of contrast-induced nephropathy, in contradistinction to the prospective data obtained from 199 patients reported by Merten et al 62 Further study will be needed to sort out this discrepancy and determine whether sodium bicarbonate is beneficial in only certain subgroups of patients. 64 Still, many recommend prophylactic sodium bicarbonate administration in high-risk patients.…”
mentioning
confidence: 99%